2016
DOI: 10.1039/c6ob01081d
|View full text |Cite
|
Sign up to set email alerts
|

Atom economical synthesis of di- and trithiocarbonates by the lithium tert-butoxide catalyzed addition of carbon disulfide to epoxides and thiiranes

Abstract: Alkali metal alkoxides were studied as catalysts for the addition of CS2 to epoxides. A screening of several commercially available alkoxides revealed lithium tert-butoxide as an active and selective catalyst for this reaction. The influence of different reaction parameters as well as the substrate scope under optimized reaction conditions has been studied. Terminal and highly substituted epoxides as well as thiiranes were converted. In total 28 products were prepared and isolated in yields up to 95%. Notably,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…And this distribution was totally determined by the tendency of O‐S ER. What is important is that, other than two common five‐membered cyclic products 5‐(phenoxymethyl)‐1,3‐ oxathiolane‐2‐thione ( C1 ) and 4‐(phenoxymethyl)‐1,3‐dithiolane‐ 2‐thione ( C2 ), phenyl thioglycidyl ether ( C3 ) was observed in the 1 H NMR spectra of crude product (Figures S3, S5, S6). Usually thiiranes are taken as the byproduct in the coupling of CS 2 with epoxides, while we think it may serve as an intermediate of O‐S ER just like COS, and its participation in the copolymerization process resulted in inequality of L1 and L2 .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…And this distribution was totally determined by the tendency of O‐S ER. What is important is that, other than two common five‐membered cyclic products 5‐(phenoxymethyl)‐1,3‐ oxathiolane‐2‐thione ( C1 ) and 4‐(phenoxymethyl)‐1,3‐dithiolane‐ 2‐thione ( C2 ), phenyl thioglycidyl ether ( C3 ) was observed in the 1 H NMR spectra of crude product (Figures S3, S5, S6). Usually thiiranes are taken as the byproduct in the coupling of CS 2 with epoxides, while we think it may serve as an intermediate of O‐S ER just like COS, and its participation in the copolymerization process resulted in inequality of L1 and L2 .…”
Section: Resultsmentioning
confidence: 93%
“…As a result, five different polymer linkages and two cyclic products were revealed by 1 H and 13 C NMR spectroscopy, and a plausible mechanism on a tetrahedral intermediate was presented based on the result of in situ infrared spectroscopic monitoring of the polymerization process. After that, Werner and his coworkers used metal alkoxide as a catalyst to mediate the reaction of CS 2 with different epoxides, and similar mechanism was proposed for O‐S ER process. In particular, catalyst loading was found to have a decisive effect on the product composition for this catalyst system.…”
Section: Background and Originality Contentmentioning
confidence: 93%
“…17 Both polymerisations are enabled by a O/S exchange reaction step in which an alkoxide chain end from a ring opened epoxide A isomerizes into a thiolate through incorporation of the oxygen into the adjacent link and this isomerised incorporated epoxide (forming a link akin insertion of a virtual thiirane) has been termed A′. 17,20 Thus, we hypothesized that other monomer combinations which undergo Li catalysed ROCOP could be suitable for sequence selective ROTERP. Xiong and coworkers very recently reported RNCS/ epoxide ROCOP mediated by a simple LiO t Bu catalyst and accordingly we hypothesised that isothiocyanates could undergo ROTERP (Fig.…”
mentioning
confidence: 99%
“…Composite films of the resulting hybrid polymers with polystyrene or poly(methyl methacrylate) might be useful as refractive ingredients. 9 Accordingly, reactions of epoxides with carbon disulfide (CS 2 have been developed) for the synthesis of cyclic dithiocarbonates (1,3-oxathiolane-2-thiones); the reactions can be performed in the presence of lithium bromide, 10 lithium tert-butoxide, 11 hydrotalcite, 12 tributylphosphine and lithium perchlorate, 13 a bimetallic aluminum(salen) complex with tetrabutylammonium bromide {[Al(salen)] 2 O•Bu 4 NBr}, 14 triethylamine, 15 aqueous 4-(dimethylamino) pyridine (DMAP), 16 DMAP and 4-methoxyphenol, 17 an N-heterocyclic carbene and potassium carbonate, 18 or triethylamine in nitromethane. 19 However, most of these reactions require high pressures and/or temperatures above the boiling point of CS 2 .…”
mentioning
confidence: 99%
“…19 The use of 5 mol% of LiO t Bu provides cyclic dithiocarbonates in high yields, although an oligomeric byproduct (~10-29%) is formed at catalyst loadings below 2.5 mol%. 11 During the course of our research on the synthesis of cyclic dithiocarbonates using several basic catalysts, we found that sixmembered cyclic amidines (Figure 1) efficiently catalyze the ring-expansion addition of epoxides with CS 2 .…”
mentioning
confidence: 99%